رقية وعوذة العقرب بين المشروع والممنوع: Ruqyah and Scorpion's Incantation between the Lawful and the Forbidden - Mohammed bin Abdul Rahman bin Salama Al-Rifai (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص الرسول صلى الله عليه وسلم رسول مرسل من عند الله ونشهد بأنه قد علمّ ما ينفع الأمة، وما تصون به نفسها عن ضرر بعض الإنس والجن والهوام والسباع؛ وأن يرقوا أنفسهم ويتعوّذوا من شرّ ذوات السموم كالعقارب وغيرها؛ وأن تكون رقيتهم وعوذتهم شرعيةً. وقد نهى -صلى الله عليه وسلم- عن الرقى الشركيّة وحذَّر منها؛ حمايةً لجانب التوحيد، ولئلا يقعوا في شباك الشرك وشره، وثمة ألفاظٌ للرقى والتعويذات ظهرت في الأوساط الإسلامية، وتناقلها بعضُ الناس قديمًا وحديثًا ظانين أنها تشفي المصابَ بلدغ العقرب؛ أو إذا تلفّظ بها مَن شَاهدَ العقربَ فإنها تحبسها فتمتنع من أذيته. وهذه الألفاظ التي يعتقد أصحابها أنها رقية وعوذة من العقرب قد انتشرت في البوادي والقرى، والتي يكثر فيها وجود العقارب وغيرها من ذوات السموم بسبب التصحّر، بل يوجد مَن يستعملها إلى يومنا علناً -أحيانا- وخفيةً -أخرى-. يهدف البحث إلى تحقيق توحيد العبادة وتعزيزه بين المسلمين. وكذلك نبذ طرق الشرك ودفع وسائله. وتصحيح الأخطاء التي تقع في توحيد العبادة وبيانها وبيان الرقى الشرعية التي يرقى بها المصاب بلدغة العقرب. ومن ثم بيان العوذات الشرعية التي يعوذ بها المسلم نفسه من لدغة العقرب ثم ذكر الرقى والعوذات غير الشرعية القديمة والمعاصرة من لدغة العقرب وبيان حكمها. وسلك الباحث المنهج الوصفي التحليلي، عزوت إلى مصادر اعتمدت عليها في بحثي من كتب السنة وغيرها وتحليلها ثم استخراج النتائج المشروع والممنوع منها. وتوصل البحث إلى ذكر الفروقات بين الرقية والعوذة وبيان أن عند اجتماعهما تكون الرقية رافعة والعوذة دافعة. بيان جواز استعمال الألفاظ المجربة النافعة في رقية والعقرب وإن لم تكن من القرآن أو الأدعية المأثورة. بيان المواثيق ومعناها. بيان حكم بعض الرقى والعوذات المستخدمة في هذا الزمان. Abstract The Prophet (Muhammad), may God’s prayers and peace be upon him, is a messenger sent from God, and we testify that he knows what benefits the nation, and what protects it from the harm of some humans, jinn, vermin and carnivores; and to protect themselves from the evil of poisonous creatures such as scorpions and others; so that their Ruqyah and their incantation be legal. And he, may God’s prayers and peace be upon him, forbade polytheistic incantations and warned against it to protect the aspect of monotheism, and lest they fall into the trap of polytheism and its evil. There are words for incantations and spells that have appeared in Islamic circles, and some ancient and modern people have transmitted them, thinking that they heal the victim from the sting of a scorpion; or if it was uttered by someone who witnessed the scorpion, then it traps it and prevents it from harming him. These words, which their owners believe are Ruqyah and incantations from the scorpion, have spread in the valleys and villages, where scorpions and other poisonous creatures are abundant due to desertification. The research aims to achieve and consolidate worship among Muslims, as well as rejecting the ways of polytheism and pushing its means. Correcting the errors that occur in the unification of worship and its clarification, and the explanation of the legal incantations with which the person injured by the sting of a scorpion is ascended. And then a statement of the legitimate invocations with which the Muslim himself seeks refuge from the sting of a scorpion, then he mentioned the ancient and contemporary incantations and illegitimate invocations from the sting of a scorpion and a statement of its ruling. The researcher followed the descriptive analytical method. I attributed the sources that I relied on in my research from the books of Sunnah and others and analyzed and then extracted the legitimate and prohibited results. The research reached to mention the differences between Ruqyah and incantation, and to show that when they are combined, Ruqyah is a lever and incantation is a motive. Explanation of the permissibility of using useful tested words in Ruqyah and the scorpion, even if they are not from the Qur’an or the aphoristic supplications, statement of charters and their meaning, explanation of the rule of some Ruqyahs and incantations used in this time.